Age-related neurochemical and behavioural changes in D409V/WT GBA1 mouse: Relevance to lewy body dementia. (October 2019) - Clarke, E.; Jantrachotechatchawan, C.; Buhidma, Y.; Broadstock, M.; Yu, L.; Howlett, D.; Aarsland, D.; Ballard, C.; Francis, P.T.
Abstract: Heterozygous mutations in GBA1, the gene which encodes the lysosomal enzyme glucocerebrosidase (GCase), are a strong genetic risk factor for the development of Lewy body dementia (LBD). Until this point however, recapitulation of the symptoms and pathology of LBD has been limited to a homozygous GBA1 mouse model which genetically and enzymatically reflects the lysosomal storage disorder Gaucher's disease. This study reports for the first time cognitive impairment by two independent behavioural tests in heterozygous GBA1 mutant mice (D409V/WT) which demonstrate significant cognitive impairment by the age of 12 months. Furthermore, reductions in GBA1 GCase enzyme activity within the brain reflects levels seen in sporadic and GBA1 mutant LBD patients. While there is no overt deposition of Lewy bodies within the hippocampus, alterations to cholinergic machinery and glial proliferation are evident, both pathological features of LBD. Interestingly, we also describe the novel finding of significantly reduced GBA2 GCase enzyme activity specifically within the hippocampus. This suggests that reduced GBA1 GCase enzyme activity dis-equilibrates the finely balanced glycosphingolipid metabolism pathway and that reductions in GBA2 GCase enzyme could contribute to the pathological and behavioural effects seen. Overall, this study presents evidence to suggest that pathological hallmarks associated with LBD specifically affecting brain regions intrinsically linked with cognition are present in the D409V/WT mice. In the absence of Lewy body deposition, the D409V/WT mice could be considered an early pre-clinical model of LBD with potential for drug discovery. Since few robust pre-clinical models of LBD currently exist, with further characterization, the mouse model described here may contribute significantly to developments in the LBD field. Highlights: Age-related cognitive impairment in heterozygous D409V/WT mutant mice. Brain GBA1 GCase enzyme activity in D409V/WT mice is comparable with LBD patients. GBA2 GCase enzyme activity is reduced in the hippocampus of D409V/WT mice. D409V/WT GBA1 mice demonstrate cholinergic dysregulation and glial proliferation. The D409V/WT mouse is a promising model for LBD study and drug discovery.